E-commerce : business, technology, society - Laudon, Kenneth C., 1944-; Traver, Carol Guercio (Upper Saddle River, N.J. : Prentice Hall, 2010)
In the 14 years since it began in 1995, electronic commerce has grown in the United States from a standing start to a $228 billion retail business and a $3.4 trillion business-to-business juggernaut, bringing about enormous change in business firms, markets, and consumer behavior.
Part 1: Introduction to e-commerce. The revolution is just beginning ; E-commerce business models and concepts -- Part 2 : Technology infrastructure for e-commerce. The Internet and Word Wide Web: e-commerce infrastructure ; Building an e-commerce web site ; Online security and payment systems -- Part 3 : Business concepts and social issues. E-commerce marketing concepts ; E-commerce marketing communications ; Ethical social and political issues in e-commerce -- Part 4: E-commerce in action. Online retailing and services ; Online content and media ; Social networks, auctions, and portals ; B2B e-commerce: supply chain management and collaborative commerce.
Includes bibliographical references (p. [R-1]-R-16) and index.
Keywords: Electronic commerce; Internet marketing; Electronic commerce -- Social aspects; Information technology